Milho fertirrigado com dejetos líquidos de suínos para ensilagem - Cesarino, Rodrigo de Oliveira (2006)
Corn silage is an alternative forage to feed cattle of good energy value and if it goes well prepared it can present equivalent nutritious value to that existed in original green material This research was led with the objective of evaluating agronomic characteristics and bromatological in corn for silage fertilized in covering with liquid dejections of swine (LDS) The experiment was installed in a private property in the municipal district of Alfenas - MG Double hybrid corn was used Geneze 2005 and corn variety (Al-Band) The experimental disign was of blocks casualized with five treatments and four blocks The treatments were T1-witness without covering manuring T2-Nitrogen and Potassium at 30-00-20 350 kg/ha T3-50 m3 LSD/ha T4-100 m3 LSD/ha and T5-150 m3 LSD/ha The obtained results were submitted to the variance analysis with test Scott-Knott at the level of significance of 5% It was evaluated the heights of plants and of ears of corn fallen ill plants or broken percentage of dry matter and production of dry matter pH rude protein (PB) fiber in neutral detergent (FDN) fiber in acid detergent (FDA) digestibility in vitro of the matter evaporates (DIVMS) lignine and ashes The largest averages of plants height were observed in treatments that received manure covering and chemical fertilizer The largest averages of corn ear height happened in the treatments that received chemical fertilizer and 100 m3 LSD/ha The largest percentage of fallen ill plants and broken it was verified in variety Al-Band (4,0%) For the cultivate Geneze 2005 the production of dry matter was 15,5% superior than the variety Al-Band The largest production of dry matter was observed in the chemical treatment (14.913 Kg MS/ha) followed by the treatment of 150 m3 LSD/ha (13.719 kg MS/ha) The medium values of dry matter were influenced by the treatments presenting variations of 30,93% (witness) and 33,83% (chemical) The pH values presented a width of 3,72 (Al-Band) to 3,75 (Geneze 2005) differentiating statistically to each other It was observed in cultivating Geneze 2005 a larger value of PB in the chemical treatment (5,98%) followed by the other treatments In the treatments witness and 150 m3 DLS/ha the largest values of FDN were observed compared with the smallest value observed in the chemical fertilizer (53,87%) The largest percentage of FDA was observed in cultivating Geneze 2005 in relation to variety Al-Band It was observed that the treatment that received the chemical fertilizer in covering presented a larger coefficient of DIVMS (54,44%) The largest values of DIVMS were observed for to cultivate Geneze 2005 in the chemical treatment suggesting relation to the largest participation of grains however the values observed for to cultivate Al-Band didn't show statistical difference Chemical fertilizer treatment showed lower statistic level for lignin in both cultivates of corn In Ash percentage the witness treatment for both corn cultivates were higher than the treatments with LDS The manure covering with liquid dejections of swine above 100 m3/ha provided satisfactory productivities and of good nutritional value in corn growing for silage This way the liquid dejections of swine can be an alternative in the manuring in covering in the culture of the corn The hybrid Geneze 2005 presented the largest productivities when compared to variety Al-Band